Health Preserving Educational Environment in the Condition for Information Technologies - Diachenko-Bohun, Maryna; Rybalko, Lina; Grygus, Igor; Zukow, Walery (Journal of History Culture and Art Research, 2019)
Information technologies in institutions of higher education is suggested, which is explained as a holistic dynamic process of organizing and stimulating the independent cognitive activity of students for mastering the skills of active transformation of the information environment, which involves the optimal use of the triad "student-teacher-librarian" consolidated personnel, logistical, educational, methodological, financial and information resources. The effectiveness of the implementation of resource-based learning in a health preserving educational environment of institutions of higher education is analyzed. The transformation of the information environment is understood as the study, analytical and synthetic analysis of the content of educational information, regrouping and changing its values and form, preparation of its new way (secondary data), convenient for future use. The implementation of information technologies in higher educational institutions with the established health preserving educational environment enables: a purposeful system of conditions for scholarly activity, which not only does any harm to the health, but also ensures its formation, preservation and strengthening in all participants of the educational process; application of active forms and methods of education aimed at creating a comfortable health-saving psychological atmosphere during classes; awareness of teachers and students about ways to preserve health and respect for their health keeping behavior; developing in students, in future specialists of value attitudes towards their own health and the health of their peers.